Community-based use of grey-water in home farming - Al-Balawenah, A.; Al-Karadsheh, E.; Qadir, Manzoor (International Center for Agricultural Research in the Dry Areas, 2011)
With annual renewable water resources of less than 150 m3 per capita, Jordan is one of the most water scarce countries of the world. The demand for freshwater resources has been on the increase in the urban sector due to the economic development and population growth. The limited amount of water available for agriculture necessitates the use of non-conventional water resources, such as gray water, as an alternate option. Gray water refers to domestic wastewater generated by baths, showers, hand basins, floor wastes, washing machines, and dishwashing, which has not been mixed by toilet wastes. Its treatment and reuse offers an attractive option in arid and semi-arid regions due to its role in promoting the preservation of high-quality freshwater, as well as reducing environmental pollution. Additional benefits include cost savings to both the consumer and state water authorities, through reduced sewage flows and potable water supplies. This resource comprises about 50-80% of house water consumption in the rural areas of Jordan. In times of unpredictable rainfall resulting from climate change, gray water provides a reliable supply of water for home farming to irrigate high-value crops, contributing to food security and income generation at the household level. Gray water reuse research activities in Jordan, conducted mainly by the National Center for Agricultural Research and Extension (NCARE) in cooperation with several national and international organizations, reveal its high potential for irrigation of residential gardens, especially in rural areas. However, there is a need for further research in gray water treatment and quality improvement to reduce environmental risks and enhance sustainable use. In partnership with the International Center for Agricultural Research in the Dry Areas (ICARDA), NCARE is addressing these aspects through community-based interventions leading to safe and productive use of gray water for crop production.